Three‐Point Bending Properties of 3D‐Printed Continuous Carbon Fiber Reinforced Heterogeneous Composites Based on Fiber Content Gradients. Issue 1 (16th September 2022) - Dou, Hao; Ye, Wenguang; Zhang, Dinghua; Wu, Chenhao; Huang, Kuidong; Sun, Tianyu; Cheng, Yunyong
Abstract : The optimized design of 3D‐printed continuous fiber reinforced composites (CFRCs) at the structural level provides the possibility of further performance improvement. Herein, a design scheme of three‐point bending heterogeneous 3D‐printed continuous carbon fiber reinforced composites (CCFRCs) based on fiber volume fraction is reported. It is found experimentally that, compared with the pure polylactic acid (PLA), the force bearing capacity of the three designed CCFRCs with different fiber volume fractions increases by 190.46%, 222.36%, and 253% with the raise of fiber content, and flexural modulus increases by 369.32%, 426.05%, and 549.41%, respectively. Another discovery is that the spatial arrangement of fibers is also an important factor affecting the bending performance, and it is concluded that the bottom region's fiber content has a significant effect on the bending performance, with the same fiber content (10.20%), the load withstood with a larger fiber volume fraction setting of the bottom layer is 117.69% of that with a smaller one. The failure modes are observed using cone beam computed tomography and the main failure causes of the structures are analyzed. Herein, a solution for the lightweight structure design is provided as well as improves its comprehensive performance, further promoting the potential application of 3D‐printed CCFRCs. Abstract : Three‐point bending properties of 3D‐printed continuous carbon fiber reinforced heterogeneous composites based on fiber content gradients are reported, and their enhanced bending mechanical performance with the reasonable arrangement of continuous fibers spatially is demonstrated. The remarkable mechanical performance draws from the combination of fiber content as well as the spatial arrangement of fibers.